The Role of Saving and Lending Cooperatives in Increasing Its Members Earning and Review Based On Islamic Law - Fathul Djannah; Muhammad Rizal (Budapest International Research and Critics University, 2019)
The papers aim is to conformity with the content and spirit of the 1945 constitution, the government of the Republic Indonesia has underlined that cooperative ventures will be the pillar and accommodation of the people’s economy. A descriptive and analytic study has been conducted through the collection the data from interviews and completed questioners of the purposive sampling method. The study has reveals the services of saving and lending cooperatives to their members as well as the community are still unsatisfactory, but it has some benefit to the members. The money saving and lending contracts can be classed as reciprocal and contain the principles of freedom to contract and equilibrium. The cooperative principles are relevant with Islamic Law. It stills no consensus in opinion among the Moslem Scholars on the rate interest in money saving and lending from the cooperative.